Assessment of snapdragon (Antirrhinum majus) germplasm for various traits - SINGH, A K; JAUHARI, SHIVA (The Indian Journal of Agricultural Sciences, 2011)
An experiment was carried out during 2003-2004 and 2001-2005 to evaluate the 21 lines of snapdragon (Antirrhinum sajum L.) for different traits. Significantly wide variation was recorded in all growth parameters. Maximum number of secondary branches I plant (21) was observed in ’PSG IS’ and number of leaves (2670.33) with ’PSG 12’, whereas lines ’PSGl’and ’PSC I ’resulted in maximum number of nodes(28.33)and leafareaindex(5.36), respectively. Allthe flowering and post harvest parameters were also significantly influenced due to various lines. Maximum number of florets /spike and number of open florets in vase were recorded with ’PSG 6’. ’PSG 20’ exhibited maximum rachis length (1 2.55 cm) whereas it showed maximum weight loss of spike in vase. Maximum opening of floret (%) was recorded in ’PSG 19’. However, ’PSG 18’ exhibited minimum weight loss (%) and maximum weight of spike at senescence, water uptake and vase life.>p/>